Group 6 transition metal dichalcogenide nanomaterials: synthesis, applications and future perspectives. Issue 2 (4th January 2018) - Samadi, Morasae; Sarikhani, Navid; Zirak, Mohammad; Zhang, Hua; Zhang, Hao-Li; Moshfegh, Alireza Z.
Abstract : Looking at the science and production methods of group 6 transition metal dichalcogenide (MoS2, WSe2, etc. ) nanomaterials from the viewpoint of technological applications. Abstract : Group 6 transition metal dichalcogenides (G6-TMDs), most notably MoS2, MoSe2, MoTe2, WS2 and WSe2, constitute an important class of materials with a layered crystal structure. Various types of G6-TMD nanomaterials, such as nanosheets, nanotubes and quantum dot nano-objects and flower-like nanostructures, have been synthesized. High thermodynamic stability under ambient conditions, even in atomically thin form, made nanosheets of these inorganic semiconductors a valuable asset in the existing library of two-dimensional (2D) materials, along with the well-known semimetallic graphene and insulating hexagonal boron nitride. G6-TMDs generally possess an appropriate bandgap (1–2 eV) which is tunable by size and dimensionality and changes from indirect to direct in monolayer nanosheets, intriguing for (opto)electronic, sensing, and solar energy harvesting applications. Moreover, rich intercalation chemistry and abundance of catalytically active edge sites make them promising for fabrication of novel energy storage devices and advanced catalysts. In this review, we provide an overview on all aspects of the basic science, physicochemical properties and characterization techniques as well as all existing production methods and applications of G6-TMD nanomaterials in a comprehensive yet concise treatment. Particular emphasis is placed on establishing a linkage between the features of production methods and the specific needs of rapidly growing applications of G6-TMDs to develop a production-application selection guide. Based on this selection guide, a framework is suggested for future research on how to bridge existing knowledge gaps and improve current production methods towards technological application of G6-TMD nanomaterials.